MISE EN SCENE DALAM MEMBANGUN ADEGAN DRAMATIK PADA FILM GRAVE TORTURE KARYA JOKO ANWAR - Nurlaily Dicha Aningtyas; Didik Suharijadi; Fajar Aji (Program Studi Film dan Televisi Universitas Jember, 2019)
This research is about mise-en-scene in building dramatic scenes in the film Grave Torture by Joko Anwar. The purpose of this research is to describe the dramatic elements in the Grave Torture film and find out the role of mise en scene in building dramatic scenes in the film Grave Torture. Research data was assessed using Elizabeth Lutters’ dramatic theory, mise-en-scene and cinematography. Dramatic elements are used to determine dramatic scenes in the film Grave Torture, while mise-en-scene and cinematography are used to analyze visual aspects in building dramatic scenes in the film Grave Torture. This research uses a qualitative research type using descriptive method. Based on the research that has been done, there are 5 dramatic scenes in the film Grave Torture. Mise-en-scene elements such as settings, costumes and make up, lighting, and the player and movement help build dramatic scenes in the film Grave Torture.